Two male patients with nevoid basal cell carcinoma syndrome from Turkey - Tümer, Celal; Er, Nuray; Balcı, Sevim; Ataç, Atilla (The Turkish Journal of Pediatrics, 2001)
Nevoid basal cell carcinoma syndrome, also known as Gorlin’s syndrome, is a familial autosomal dominant syndrome characterized by multiple basal cell carcinomas, multiple odontogenic keratocytes of the jaws, and skeletal anomalies. Both tumors and malformations of the central nervous system occur with nevoid basal cell carcinoma. Medulloblastoma is the primary brain tumor most frequently associated with this syndrome. The authors report in this article two male patients with nevoid basal cell carcinoma syndrome: a 22-year-old male patient with multiple odontogenic keratocytes, who had medulloblastoma at two years and multiple basal cell carcinoma at 10 years of age, and a 15-year-old male patient with skeletal abnormalities and multiple odontogenic keratocytes in the jaws.